Mainstream Education of the Hearing Impaired in Mysore City : A Report - Indira Prakash (Journal of All India Institute of Speech and Hearing, 1970)
Mainstreaming Education is a system of education where the hearing impaired children are educated in normal schools. The main objective is to prepare these children to adjust to socio cultural  environment, to derive satisfaction and to experience success academically. This report gives the analysis of a survey of 70 children in the integrated school education system. The survey aimed to analyze  the practice of integration of hearing  impaired children and the shortcomings in the implementation of this system. Several recommendations  have been made to  streamline  the system